2017
DOI: 10.1187/cbe.17-01-0023
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Undergraduate Biology Students in Scientific Modeling: Analysis of Group Interactions, Sense-Making, and Justification

Abstract: This paper provides an analysis on how undergraduate students work together, justify their ideas, and make sense of key ideas during in-class scientific modeling activities in large-lecture classrooms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…At the undergraduate level, MBI has been described in chemistry (Khan, 2007; Tien et al , 2007; Walker et al , 2011) and physics (Brewe, 2008; Zwickl et al , 2014). In undergraduate biology, curricula have been developed for content-based courses that engage students in developing conceptual models (Speth et al , 2014; Bierema et al , 2017; Baze and Gray, 2018) or using models to aid in interpretation of data (Zagallo et al ., 2016). Svoboda and Passmore (2010) also described a small-enrollment course for biology students to engage in authentic mathematical modeling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the undergraduate level, MBI has been described in chemistry (Khan, 2007; Tien et al , 2007; Walker et al , 2011) and physics (Brewe, 2008; Zwickl et al , 2014). In undergraduate biology, curricula have been developed for content-based courses that engage students in developing conceptual models (Speth et al , 2014; Bierema et al , 2017; Baze and Gray, 2018) or using models to aid in interpretation of data (Zagallo et al ., 2016). Svoboda and Passmore (2010) also described a small-enrollment course for biology students to engage in authentic mathematical modeling.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Clement (2008) demonstrated that asking a student to develop models supported conceptual change. Other studies have shown how a modeling approach could encourage students’ sense-making in a classroom setting (Stewart et al , 2005; Bierema et al , 2017). Based on what we understand about MBR among experts, it has been suggested that the ability to conduct productive mental modeling develops with learning in a domain (Ippolito and Tweney, 1995; Nersessian, 2002), further emphasizing the importance of allowing students to practice this skill through schooling.…”
Section: Introductionmentioning
confidence: 99%
“…Our study built on and shared similarities to work in other contexts such as a chemistry PLTL course (Repice et al, 2016) and biology courses taught using cooperative learning (Bierema et al, 2017) or peer instruction (Knight et al, 2013). Our findings, however, are limited to our experience with one specific course and one subject area over the course of only one semester in one institution and reflect only certain functions of student discourse.…”
Section: Conclusion and Recommendations For Practicementioning
confidence: 89%
“…Work in other collaborative learning contexts, however, has been informative. Bierema et al (2017) analyzed group discussions during modeling activities in an introductory biology course and found that team members commonly co-constructed their knowledge during modeling activities and engaged in sense-making interactions to build their understanding of the biological model. Similarly, Knight et al (2013) found that the majority of student discussions of clicker questions in an upperlevel biology class used evidence-based reasoning, and questions that requested or required student reasoning were more likely to produce it.…”
Section: Introductionmentioning
confidence: 99%
“…The modular nature of this laboratory exercise lends itself to a modeling strategy where students can create a working model that is continually revised. Modeling has been successful in large introductory biology courses and is applicable to retention of multistep processes . Likewise, metacognition strategies could be employed to provide space to think dynamically about each individual component and the project as a whole .…”
Section: Discussionmentioning
confidence: 99%